PENGAWASAN BADAN NARKOTIKA NASIONAL (BNN) DALAM MENANGGULANGI PENYALAHGUNAAN NARKOBA DIKOTA PEKANBARU - Setiawan, Ryan; ", Isril (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Ryan Setiawan (1001112089), Oversght of National Narcotic (BNN) in tackling drug abuse in the city of Pekanbaru, Adviser by Drs. H. Isril, MH. Supervision which has been run by BNN Pekanbaru in performing its functions as a designated agency to tackle drug abuse in the city of Pekanbaru has been going well , but there are some indicators that still have not been able to run well . Indicators of employment report could not walk properly because the BNN reporting directly down the center of spaciousness that BNN Pekanbaru not have a concrete statement about the problem of drug abuse in the city of Pekanbaru . In the absence of such reports affect performance in terms of Pekanbaru City BNN supervision . According to Griffin supervision is part of the management function that seeks to predefined plans can be achieved effectively and efficiently , in the process of supervision Griffin has set the standard three steps are set standards , conduct assessments, and conduct corrective action. This study is a descriptive qualitative approach in which the author describes the supervision of BNN in tackling drug abuse in Pekanbaru and the factors that influence the control of drug abuse . Data collection technique is by interview and observation by using purposive sampling method . Key informants in this study is Kasubbag BNN Pekanbaru City Administration . The results of the study authors was an oversight that has been run by BNN Pekanbaru City in exercising its functions as an agency that oversees drug abuse in Pekanbaru has been going well but there are some indicators that are still not maximized because supervision is not done routinely and uniformly in all circles so much abuse drugs in the city of Pekanbaru .Keywords : Monitoring , Drugs